Merawat Tradisi Bersih Desa: Upaya Kearifan Lokal Menghadapi Kekeringan di Kecamatan Bandar - Wendahayu, Yayan; Aorta, Dian Tias (YASIN, 2025)
This research aims to examine the Clean Village tradition as a form of local wisdom in dealing with drought in Ngunut Village, Bandar District, Pacitan Regency. Prolonged drought has become a serious challenge for local communities, affecting clean water needs and economic activities. Through a qualitative approach with descriptive methods, this research explores the role of the Clean Village tradition in strengthening social, spiritual solidarity and community environmental awareness. Data collection was carried out through interviews with village elders and the community, participatory observation, and documentation of activities. The research results show that the Clean Village tradition not only functions as a sustainable cultural heritage, but also has pragmatic value in dealing with drought problems. This tradition is a moment of collective reflection and a symbolic effort to ask for rain, as well as strengthen the community's social relations in protecting the surrounding environment. The success of Petungsinarang Village with the government's pipeline and drilled well program shows that the synergy between local wisdom and modern programs can provide sustainable solutions.